Are Bioactive Materials Necessary for Patients with Low Caries Risk? A Case Series of Incipient Enamel Carious Lesions in Anterior and Posterior Teeth - Wang, Linda; Giacomini, Marina Ciccone; Costa, Mylena Proença; Foratori Junior, Gerson Aparecido; Zabeu, Giovanna Speranza; Mosquim, Victor (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Over the past decades, advancements in the understanding of caries disease mechanisms have led professionals to adopt the principles of Minimal Intervention Dentistry. These principles emphasize that management should primarily address the disease’s etiological factors, allowing for the maximum preservation of remineralizable dental structures, ultimately enhancing tooth longevity and reducing disease burden. Meanwhile, numerous dental materials with bioactive properties have been developed, and current marketing strategies often present these materials as essential for effective treatment. Consequently, some professionals may perceive their approach as outdated if they do not incorporate bioactive materials. This study presents a series of cases involving incipient enamel carious lesions in both anterior and posterior teeth that were successfully treated regardless of the use of bioactive materials. The findings demonstrate that, when the disease's etiological factors are properly controlled, bioactive materials are not indispensable.